Determinants of HDL Cholesterol Efflux Capacity after Virgin Olive Oil Ingestion: Interrelationships with Fluidity of HDL Monolayer. Issue 12 (26th October 2017) - Fernández‐Castillejo, Sara; Rubió, Laura; Hernáez, Álvaro; Catalán, Úrsula; Pedret, Anna; Valls, Rosa‐M; Mosele, Juana I.; Covas, Maria‐Isabel; Remaley, Alan T.; Castañer, Olga; Motilva, Maria‐José; Solá, Rosa
Abstract : Scope: Cholesterol efflux capacity of HDL (CEC) is inversely associated with cardiovascular risk. HDL composition, fluidity, oxidation, and size are related with CEC. We aimed to assess which HDL parameters were CEC determinants after virgin olive oil (VOO) ingestion. Methods and results: Post‐hoc analyses from the VOHF study, a crossover intervention with three types of VOO. We assessed the relationship of 3‐week changes in HDL‐related variables after intervention periods with independence of the type of VOO. After univariate analyses, mixed linear models were fitted with variables related with CEC and fluidity. Fluidity and Apolipoprotein (Apo)A‐I content in HDL was directly associated, and HDL oxidative status inversely, with CEC. A reduction in free cholesterol, an increase in triglycerides in HDL, and a decrease in small HDL particle number or an increase in HDL mean size, were associated to HDL fluidity. Conclusions: HDL fluidity, ApoA‐I concentration, and oxidative status are major determinants for CEC after VOO. The impact on CEC of changes in free cholesterol and triglycerides in HDL, and those of small HDL or HDL mean size, could be mechanistically linked through HDL fluidity. Our work points out novel therapeutic targets to improve HDL functionality in humans through nutritional or pharmacological interventions. Abstract : Determinants for high‐density lipoprotein (HDL) cholesterol efflux capacity (CEC) are assessed. Post‐hoc analyses from data of a crossover intervention with three types of virgin olive oil (VOO) are performed to assess the relationship of 3‐week changes in HDL‐related variables after intervention periods. HDL fluidity, ApoA‐I concentration, and oxidative status were major determinants for CEC after VOO. The impact on CEC of an increase in HDL‐free cholesterol and HDL mean size, and a reduction in HDL‐triglycerides and small HDL particle number could be mechanistically linked through HDL fluidity.